hubungan pendidikan karakter terhadap hasil belajar siswa kelas vii smptk mentari pahae julu tahun pelajaran 2023-2024 - Juwita LC Silaban; Sri Utami Kholilla Mora Siregar; Eni Sumanti Nasution (Universitas Gara Nusantara Padangsidimpuan, 2024)
This research method uses quantitative research, the instruments used are questionnaires and documentation. The population in this study was class VII students, totaling 34 students with a sample of 34 from the class. Samples were taken using proportionate stratified random sampling technique. Data analysis used in this research uses data analysis and interviews. The results of the research that has been carried out state that the faining table means that both data before and after using character education are significant, and the sig value is 0.542 496 which means Ho is rejected and H1 is accepted. So there is A significant relationship between character education and student learning outcomes in Class VII Physics at SMPTK Mentari Pahae Julu Padangsisimpuan Academic Year 2023/2024.